2015
DOI: 10.1007/s00417-015-3066-3
|View full text |Cite
|
Sign up to set email alerts
|

Changes in macular layers in the early course of non-arteritic ischaemic optic neuropathy

Abstract: Changes in the thickness of different layers of the retina occur early in the course of AION and evolve over time, resulting in the atrophy of the GCL and RNFL. ONL thickening at baseline is associated with visual dysfunction. Thinning of the GCL after 1 month correlates with poorer VF and BCVA at 1 month after acute AION.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 20 publications
0
18
1
Order By: Relevance
“…Because previous studies have reported that thinning of the macula and ganglion cell layer occurs as early as one month following the onset of NAION [14, 15], this result was not expected. One possible reason for this result is due to the different composition of central and peripheral retina.…”
Section: Discussionmentioning
confidence: 88%
“…Because previous studies have reported that thinning of the macula and ganglion cell layer occurs as early as one month following the onset of NAION [14, 15], this result was not expected. One possible reason for this result is due to the different composition of central and peripheral retina.…”
Section: Discussionmentioning
confidence: 88%
“…Furthermore, the results obtained from the custom built UHR-OCT may limit the generalization of our current findings. However, the Orion Software used in the present study has been adapted in commercial OCT devices such as Zeiss Cirrus HD-OCT (with special data exportation), 44,45 Topcon 3D-1000 (Topcon Medical Systems, Inc., Oakland, NJ, USA), 46 and Spectralis SD OCT (Heidelberg Engineering, Heidelberg, Germany). 47 Our study can be repeated using these commercial OCT devices and the Orion software.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, these commercially available OCT devices generate automated thickness maps for only limited layers such as TRT and GCIPL thicknesses 21,31,32. The advances in automated and semiautomated segmentation have facilitated delineation of multiple intraretinal layers in three dimensions 27,29,30,33,34. However, with the exception of Orion, a software that automates the thickness mappings of six to eleven intraretinal layers is not commercially available.…”
Section: Discussionmentioning
confidence: 99%
“…However, with the exception of Orion, a software that automates the thickness mappings of six to eleven intraretinal layers is not commercially available. Orion has been previously applied in processing volumetric data obtained from a commercial device (Cirrus HD-OCT), segmenting in this case, the thickness maps of six retinal layers 29. The software was adapted to our custom OCT, prompting our need for testing the repeatability of the intraretinal thicknesses ahead of performing further clinical studies.…”
Section: Discussionmentioning
confidence: 99%